Determinants of Small and Rural Local Governments’ Renewable Energy Program Adoption in Cascadia - Steel, Brent Steven; Wolters, Erika Allen; Krawchenko, Tamara; Farooq, Sadaf (Current Alternative Energy, 2024)
AimThis study aimed to investigate the determinants of renewable energy policy adoption by small and rural local governments in Cascadia.BackgroundSmall and rural local governments currently face many ongoing and numerous new challenges that complicate their task of sustaining current public services and programs. How government officials adapt to these changes can affect the long-term viability of local governments in both the U.S. and Canadian contexts.ObjectiveThis study has examined the presence or absence of renewable energy programs in small and rural local governments in the “Cascadia” region of Canada and the U.S. (British Columbia, Oregon, and Washington).MethodsUsing surveys and interviews of Cascadia local government leaders during the summer and fall of 2023, correlates of renewable energy policy adoption have been examined, including cultural, demographic, economic, and political factors.ResultsKey findings have indicated cities, experiencing population growth, and those with a progressive political orientation to be more inclined to adopt renewable energy policies. Conversely, remote communities have demonstrated a lower propensity for such adoption. Financial constraints, evidenced by the impact of inflation and the necessity for service cutbacks, have been found to negatively correlate with the consideration of renewable energy policies.ConclusionThis study has indicated renewable energy projects to be more often found or contemplated in areas being politically liberal, densely populated, and not predominantly rural. It could be beneficial in shifting the perception of renewable energy from being predominantly an environmental concern to being recognized for its economic benefits.
Keywords: population dynamics